Adolescents' Perception of HIV Testing - Fenska Narly Makualaina; Crystin Evangelin Watunglawar; Angela Librianti Thome; Nasri Nasri; Innal Saitis (Indonesian Journal of Global Health Research, 2026)
This research aims For understand perception teenager about HIV testing at Sentani Health Vocational School as well as identify factors that influence perception said. Research methods use approach qualitative with design phenomenology. Participants study amount to four teenagers , consisting of of two men and two women 14 until 15 years old. Data is collected through interview in-depth and Focus Group Discussion (FGD), then analyzed use analysis thematic. Research results show there is seven theme main: characteristics teenagers, knowledge teenager about HIV and HIV testin, perception teenager to HIV test, trust to accuracy results HIV test, importance HIV test for teenagers, the importance of education about HIV testing, and the impact HIV test for decision teenager in health reproduction. This study concludes that teenager Still own knowledge limited and diverse perceptions to HIV test.